1961
DOI: 10.1037/h0049210
|View full text |Cite
|
Sign up to set email alerts
|

Some factors in the programming of conceptual learning.

Abstract: Studies of conceptually mediated behavior in human beings are often concerned with the effects of variations in previously established concepts on behavior in the solution of problems. This is true, for example, of the work of Maier (1930) with practical problems; of Luchins (1942) on water-jar problems; and of Maltzman and his collaborators (Malzman, Eisman, Brooks, & Smith, 1956;Maltzman & Morrisett, 1952, 1953a v , 1953b on anagrams; to mention a few well-known investigations. Usually, in such studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

1966
1966
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(51 citation statements)
references
References 17 publications
3
47
0
1
Order By: Relevance
“…This "hierarchical" type of structure has been advocated for use in classroom instruction by educational psychologists in order to make material more comprehensible (Briggs, 1968;Gagne, 1970;Gagne & Brown, 1961;Gagne & Rohwer, 1969). Several researchers have shown the effectiveness of such a method in controlled situations (Eustace, 1969;Lee, 1968) and have shown that the more complex the task is, the smaller and simpler the component steps should be (Naylor & Briggs, 1963).…”
Section: Organization Of Contentmentioning
confidence: 95%
“…This "hierarchical" type of structure has been advocated for use in classroom instruction by educational psychologists in order to make material more comprehensible (Briggs, 1968;Gagne, 1970;Gagne & Brown, 1961;Gagne & Rohwer, 1969). Several researchers have shown the effectiveness of such a method in controlled situations (Eustace, 1969;Lee, 1968) and have shown that the more complex the task is, the smaller and simpler the component steps should be (Naylor & Briggs, 1963).…”
Section: Organization Of Contentmentioning
confidence: 95%
“…Roe (1962), using a longer version of the Roe et al (1962) statistics program, found that subjects receiving ordered instruction made fewer errors in learning and performed slightly but significantly better on a posttest. The most striking instance of inferior performance due to scrambling was reported by Brown (1970) in which subjects who learned the Gagn6 and Brown (1961) series sum program in scrambled order performed significantly worse on measures of learning ease and transfer. Unfortunately, the differences cited in the latter two studies were quite small and larger transfer tests would certainly be useful in further investigations.…”
Section: Learning Ease Retention and Transfer Of Conceptual Learningmentioning
confidence: 96%
“…Finally, in a study by Gagne and Brown (1961), students learned to derive formulas and solve series sum problems such as how to compute the sum of "1, 3, 5, 7, 9. . .…”
Section: Strike One: Discovery Of Problemsolving Rulesmentioning
confidence: 99%